Exploring New Ingredients and Technologies in Order to Enhance the Quality of Gluten Free Bakery Products: Innovations for Gluten-free Bread Production (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Wheat bread is eaten worldwide and has played an significant role in society history since agriculture grew. Although most people prefer to enjoy and fulfil the fragrance and taste of this staple product, certain individuals have a special aversion to wheat or a hereditary propensity to celiac disease. To enhance the quality of life of these people, food manufacturers have sought to produce good quality gluten-free bread from a nutritional viewpoint. As the consistency of the wheat breads depends in large part on the viscoelastic properties of gluten, several additives, including hydrocolloids, transglutaminases and proteases, were used to intensify their effectiveness. Latest efforts also involved the usage of redox and particle-stabilized foam control. We are discussing the success in the production of gluten free bread by our laboratory and others, with an emphasis on rice-based breads.